2013
DOI: 10.1108/14608791311310519
|View full text |Cite
|
Sign up to set email alerts
|

Physical barriers and risks in basic activities of daily living performance evaluation in state housing for older people in Chile

Abstract: Autor no autoriza el acceso a texto completo de su documentoPurpose – This paper aims to describe an evaluation instrument designed to detect physical barriers and risks in basic activities of daily living (BADLs) performance by senior citizens and presents findings obtained in a representative sample of older persons living in housing programs provided by the State of Chile. Its aim is to develop an objective instrument which can serve as reference point for housing adaptations and improvement or for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Moreover, the present study provides evidence for more progressive political action regarding housing provision that meets 18 the needs of the ageing population. Efforts in the building industry and public agencies should target ways to enhance active and healthy ageing, as argued in previous research [4,30,51]. To meet the needs of accessible housing every effort to rebuild and upgrade the existing ordinary housing stock must be based on the best possible knowledge, calling for more research in this area [29].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the present study provides evidence for more progressive political action regarding housing provision that meets 18 the needs of the ageing population. Efforts in the building industry and public agencies should target ways to enhance active and healthy ageing, as argued in previous research [4,30,51]. To meet the needs of accessible housing every effort to rebuild and upgrade the existing ordinary housing stock must be based on the best possible knowledge, calling for more research in this area [29].…”
Section: Discussionmentioning
confidence: 98%
“…Based on the scientific evidence available [21,23,51], also functioning in terms of ADL capacity would be positively affected [17]. Since older people often want to live at home as long as possible [52], this is of importance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the impact of general cognitive functioning (S-MMSE) on everyday task performance, in addition to the contribution of physical and sensory impairment (Seidel et al, 2011) and the environment (Pizzi et al, 2013), one explanation for these variations could be that different cognitive areas are associated with performance on different basic ADLs, rather than all activities. Although many studies have explored the relationship between cognitive functions, such as different forms of memory or executive functioning (Earnst et al, 2001;Razani et al, 2007), and instrumental ADLs (IADLs; Lawton and Brody, 1969), including household tasks, laundry, meal preparation, finance and medication management, shopping, telephoning, and transport, little or no attention has been paid to the cognitive underpinnings of basic ADLs as evaluated here.…”
Section: Discussionmentioning
confidence: 99%
“…Maneuverability involves features that could affect ease of use, such as the weight and height of doors and windows (Figure 6). Pizzi et al (2013) identified that inadequate heights of essential elements such as cabinets and electrical outlets affected QOL. Walkability encouraged older people to go out independently and offered opportunities to exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of doorsills and nonslip treads on stairs are recommended (Currin et al, 2012). Stair unevenness has been found to be one of the main architectural barriers hindering the performance of basic daily activities in Chile’s senior state housings (Pizzi et al, 2013).…”
Section: Resultsmentioning
confidence: 99%